Adsorption filter

By adjusting the pore structure and binder ratio of activated carbon molded body, the problems of insufficient ultrafine particle removal performance and high water resistance in the prior art are solved, and good water-through properties and high efficiency ultrafine particle removal performance suitable for water purification filters are achieved. .

CN115335143BActive Publication Date: 2024-12-17KURARAY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180024815.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-01
Filing Date
2021-09-21
Publication Date
2024-12-17
Estimated Expiration
2041-09-21

AI Technical Summary

Technical Problem

The existing activated carbon molded adsorption filters have insufficient performance in removing ultrafine particles and have high water-flow resistance, so they are not suitable for use in water purification filters and other purposes.

Method used

By adjusting the pore structure of the activated carbon molded body, the specific method is to control the pore volume with a pore diameter of more than 10 μm in the range of 0.10 cm3/cc to 0.39 cm3/cc, or the pore volume with a pore diameter of less than 7 μm in the range of 0.15 cm3/cc or above, combined with the appropriate binder ratio, the density of the filter and the adsorption amount of benzene saturation are optimized to take into account the water-through properties and ultrafine particle removal performance.

Benefits of technology

It achieves good water-through properties and excellent ultrafine particle removal performance, and is suitable for use in applications such as water purification filters, reducing the risk of blockage and water-through resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115335143B_ABST
    Figure CN115335143B_ABST
Patent Text Reader

Abstract

The adsorption filter of the present invention is an adsorption filter comprising a molded body containing activated carbon and a binder, and the adsorption filter has a volume-based pore diameter of 10 μm or more and a pore volume of 0.10 cm 3 / cc~0.39cm 3 / cc adsorption filter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adsorption filter comprising a shaped body, the shaped body comprising activated carbon and a binder. Background Art

[0002] In recent years, there has been an increasing focus on the safety and hygiene of tap water quality, and there is a desire to remove harmful substances such as free residual chlorine, VOCs (volatile organic compounds) such as trihalomethanes, pesticides, and moldy odors contained in tap water.

[0003] In order to remove such harmful substances, adsorption filters comprising activated carbon shaped bodies are usually used.

[0004] It is expected that the adsorption filter including the activated carbon molded body also has the performance of removing the turbidity components (particulate matter) contained in the tap water. For this purpose, for example, Patent Document 1 discloses a method for manufacturing a turbidity reduction filter body that can be used for a longer period of time by adjusting the hardness difference between the inflow filter material part and the outflow filter material part of the activated carbon molded body. In addition, for example, Patent Document 2 discloses a water purification filter element having an activated carbon molded body and a non-woven fabric, which can take into account both high turbidity removal performance and sufficiently long clogging life. In addition, for example, Patent Document 3 discloses an activated carbon molded body formed by molding a mixture of powdered activated carbon (a) having a center particle size of 80μm to 120μm and a standard deviation σg in the particle size distribution of 1.3 to 1.9 and a fibrous binder (b). According to the activated carbon molded body of Patent Document 3, it is recorded that the removal ability of free residual chlorine, volatile organic compounds, CAT and 2-MIB is excellent, and the turbidity filtering ability is also excellent.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Publication No. 2015-033680

[0008] Patent Document 2: Japanese Patent Publication No. 2016-140788

[0009] Patent Document 3: International Publication No. 2011 / 016548 Summary of the invention

[0010] An object of the present invention is to provide an adsorption filter having excellent ultrafine particle removal performance while maintaining good water permeability.

[0011] The present inventors have intensively studied to solve the above-mentioned problems and have achieved the present invention as a result.

[0012] An adsorption filter according to one aspect of the present invention is an adsorption filter comprising a molded body containing activated carbon and a binder, wherein the adsorption filter has a volume-based pore volume of 0.10 cm-1 or more of pores having a diameter of 10 μm or more measured by mercury intrusion porosimetry. 3 / cc~0.39cm 3 / cc.

[0013] Alternatively, another aspect of the present invention relates to an adsorption filter comprising a molded body containing activated carbon and a binder, wherein the adsorption filter has a volume-based pore volume of 0.15 cm2 with a pore diameter of 7 μm or less as measured by mercury intrusion. 3 / cc or more, and the total pore volume of the adsorption filter measured by mercury intrusion porosimetry is 0.50 cm 3 / cc~0.73cm 3 / cc. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A perspective view showing one example of a template for producing the adsorption filter according to the present embodiment is shown.

[0015] Figure 2 It means use Figure 1 A perspective view of an example of an adsorption filter according to the present embodiment obtained by using a template.

[0016] Figure 3 This is a diagram for explaining a method of cutting out a sample when measuring the pore volume and the pore mode diameter of an adsorption filter.

[0017] Figure 4 This is a diagram for explaining a method of cutting a measurement sample when measuring the particle size distribution of activated carbon (carbonized product after heat treatment) in an adsorption filter.

[0018] Figure 5 A perspective view showing an example of an automatic grinding machine for manufacturing an adsorption filter.

[0019] Figure 6 This is a graph showing the pore mode diameter of the adsorption filter and the pore volume in the region.

[0020] Figure 7 This is a graph showing the correlation between the pore volume of an adsorption filter having a pore diameter of 10 μm or more and the ultrafine particle removal performance.

[0021] Figure 8 This is a graph showing the correlation between the pore volume of the adsorption filter having a pore diameter of 7 μm or less and the ultrafine particle removal performance. DETAILED DESCRIPTION

[0022] In the activated carbon molded bodies of Patent Documents 1, 2, and 3, the turbidity removal performance is evaluated. Generally speaking, the turbidity removal performance test of the filter of the activated carbon molded body is specified in JIS S 3201:2019, for example. In this test, kaolin of about 1 μm to 20 μm is used as a turbidity component (particulate matter) and its removal performance is evaluated. In the evaluation of the activated carbon molded bodies of Patent Documents 1, 2, and 3, the turbidity removal performance is also evaluated based on this test.

[0023] However, recently, from the perspective of further safety and hygiene, adsorption filters including activated carbon molded bodies are required to have the ability to remove fine particles (generally, particle sizes are 1 μm to 20 μm), and are also required to have the ability to remove ultrafine particles below 1 μm.

[0024] Activated carbon molded bodies include wet molded bodies and dry molded bodies according to their manufacturing methods. The density of wet molded bodies is relatively low, and there is a tendency for low water flow resistance, and the removal performance of organic compounds that are generally considered to be harmful is also excellent. However, due to its low density and low water flow resistance, it is predicted that it is difficult to have the performance of removing ultrafine particles. On the other hand, the density of dry molded bodies is higher than that of wet molded bodies. Therefore, ultrafine particle removal performance can be expected, but due to the increase in water flow resistance, it is not suitable for use in water purification filters and the like. Therefore, an adsorption filter including an activated carbon molded body that can have both low water flow resistance and ultrafine particle removal performance is required.

[0025] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described herein, and various modifications can be made within the scope that does not impair the spirit of the present invention.

[0026] The adsorption filter of the present embodiment is an adsorption filter including a molded body containing activated carbon and a binder, wherein the volume-based pore volume of the adsorption filter having a pore diameter of 10 μm or more measured by mercury intrusion porosimetry is 0.10 cm 3 / cc~0.39cm 3 / cc.

[0027] Alternatively, another adsorption filter of the present embodiment is an adsorption filter comprising a molded body containing activated carbon and a binder, wherein the adsorption filter has a volume-based pore volume of pores having a diameter of 7 μm or less measured by mercury intrusion porosimetry of 0.15 cm 3 / cc or more, and the total pore volume of the adsorption filter measured by mercury intrusion porosimetry is 0.50 cm 3 / cc~0.73cm 3 / cc.

[0028] By having the above-mentioned configuration, it is possible to provide an adsorption filter having excellent ultrafine particle removal performance while maintaining good water permeability.

[0029] Specifically, by appropriately selecting and adjusting the physical properties and proportion of the raw activated carbon, and appropriately controlling the void volume in the filter, the pore volume above the specified pore diameter is adjusted to be within a specific range. As a result, both water permeability and ultrafine particle removal performance can be achieved.

[0030] [Physical properties of adsorption filters]

[0031] The adsorption filter of the present embodiment has a volume-based pore volume of pores with a diameter of 10 μm or more (hereinafter also referred to as “pore volume with a diameter of 10 μm or more”) of 0.10 cm 3 / cc~0.39cm 3 / cc. By setting the pore volume of pores with a diameter of 10 μm or more to 0.10 cm 3 / cc or more, the adsorption filter of the present embodiment can maintain good water permeability. By setting the pore volume of pores with a pore diameter of 10 μm or more to 0.39 cm 3 / cc or less, and thus, in the adsorption filter of the present embodiment, the ultrafine particle removal performance is remarkably excellent.

[0032] The pore volume of the pore with a diameter of 10 μm or more is preferably 0.37 cm 3 / cc or less, more preferably 0.35cm 3 / cc or less, more preferably 0.33cm 3 The pore volume of pores with a diameter of 10 μm or more is preferably 0.12 cm 3 / cc or more, more preferably 0.15cm 3 / cc and above.

[0033] In addition, the adsorption filter of the present embodiment preferably has a total pore volume based on volume measured by mercury intrusion porosimetry (hereinafter also referred to as “total pore volume”) of 0.50 cm 3 / cc~0.73cm 3 / cc. By setting the total pore volume to 0.50 cm 3 / cc or more, the adsorption filter can obtain more excellent water permeability and is suitable for use in applications such as water purification filters. 3 / cc or less, a sufficient amount of activated carbon can be retained to achieve good adsorption performance as a general filter.

[0034] The total pore volume is more preferably 0.53 cm 3 / cc or more, more preferably 0.56cm 3 / cc or more. In addition, the total pore volume is more preferably 0.70 cm 3 / cc or less, more preferably 0.67cm 3 / cc or less.

[0035] Alternatively, in another embodiment of the adsorption filter, the volume-based pore volume of the adsorption filter with a pore diameter of 7 μm or less (hereinafter, also referred to as “pore volume with a pore diameter of 7 μm or less”) measured by mercury intrusion porosimetry is 0.15 cm 3 / cc or more and the total pore volume is 0.50cm 3 / cc~0.73cm 3 / cc. By setting the pore volume of the pores with a diameter of 7 μm or less to 0.15 cm 3 / cc or more, the ultrafine particle removal performance of the adsorption filter of this embodiment is remarkably excellent. At the same time, by setting the total pore volume to 0.50cm 3 / cc~0.73cm 3 / cc, the adsorption filter can maintain good water permeability and can improve the adsorption performance as a general filter.

[0036] The pore volume of the pores with a diameter of 7 μm or less is preferably 0.16 cm 3 / cc or more, more preferably 0.17cm 3 / cc or more, more preferably 0.18cm 3 In addition, the upper limit of the pore volume with a pore diameter of 7 μm or less is not particularly limited. For example, the pore volume with a pore diameter of 7 μm or less is preferably 0.30 cm 3 / cc or less, more preferably 0.28cm 3 / cc or less.

[0037] In addition, the preferred upper limit numerical value and lower limit numerical value of the total pore volume of the adsorption filter of another present embodiment are the same as those of the adsorption filter in the above-mentioned embodiment.

[0038] In another embodiment of the adsorption filter, it is preferred that the pore volume of the pores with a pore diameter of 10 μm or more is 0.10 cm 3 / cc~0.39cm 3 / cc, and the pore diameter of the adsorption filter is 7 μm or less and the pore volume is 0.15 cm 3 / cc or more, and the total pore volume is 0.50cm 3 / cc~0.73cm 3 In other words, it is preferable that the adsorption filter satisfies both conditions specified in the above two embodiments.

[0039] Moreover, the adsorption filter of the present embodiment preferably has a ratio of pore volume with a pore diameter of 10 μm or more to the total pore volume of 12% or more. By setting the ratio of pore volume with a pore diameter of 10 μm or more to 12% or more, the adsorption filter can obtain a more excellent ultrafine particle removal performance. The ratio of pore volume with a pore diameter of 10 μm or more is more preferably 15% or more, further preferably 20% or more, particularly preferably 25% or more, and most preferably 30% or more. In addition, the ratio of pore volume with a pore diameter of 10 μm or more is preferably 80% or less, more preferably 65% ​​or less, and further preferably 60% or less.

[0040] In addition, the adsorption filter of the present embodiment preferably has a ratio of pore volume with a pore diameter of 7 μm or less to the total pore volume of 22% or more. By setting the ratio of pore volume with a pore diameter of 7 μm or less to 22% or more, the adsorption filter can obtain a more excellent ultrafine particle removal performance. The ratio of pore volume with a pore diameter of 7 μm or less is more preferably 25% or more. In addition, the ratio of pore volume with a pore diameter of 7 μm or less is preferably 48% or less, and more preferably 45% or less.

[0041] The adsorption filter of this embodiment preferably has a pore mode diameter measured by mercury intrusion (hereinafter also referred to as "pore mode diameter") of 15 μm or less. By setting the pore mode diameter to 15 μm or less, the adsorption filter can obtain better ultrafine particle removal performance.

[0042] The pore mode diameter is more preferably 13 μm or less, and further preferably 11 μm or less. The lower limit of the pore mode diameter is not particularly limited, as long as the pore mode diameter does not become extremely small and has a significant impact on the water permeability of the filter. For example, the pore mode diameter is preferably 6 μm or more, and more preferably 7 μm or more.

[0043] In this specification, the pore volume with a pore diameter of 10 μm or more, the pore volume with a pore diameter of 7 μm or less, the total pore volume and the pore mode diameter measured by mercury intrusion can be measured using a mercury intrusion pore volume measuring device ("MicroActive AutoPore V9620" manufactured by Micromeritics) as described in the examples described later. In addition, based on the measured values ​​of these pore volumes, the ratio (%) of the pore volume with a pore diameter of 10 μm or more to the total pore volume and the ratio (%) of the pore volume with a pore diameter of 7 μm or less to the total pore volume can be calculated. It should be noted that in the examples described later, a 1 cm square size of the molded layer of the filter is used as a measurement sample, but it is preferred to appropriately change the size of the measurement sample according to the filter size. For example, if it is a faucet-mounted filter, it is preferred to use a measurement sample of about 5 mm square for measurement.

[0044] The pore volume with a pore diameter of 10 μm or more, the pore volume with a pore diameter of 7 μm or less, the total pore volume and the pore mode diameter of the adsorption filter of the present embodiment as described above can be controlled by various methods. It should be noted that by controlling the value of the pore volume, the ratio of the pore volume with a pore diameter of 10 μm or more to the total pore volume and the ratio of the pore volume with a pore diameter of 7 μm or less to the total pore volume can also be controlled simultaneously. For example, by appropriately selecting and appropriately adjusting the physical properties of the raw activated carbon and its blending amount, their blending ratio when using two or more activated carbons with different physical properties, the type of raw binder and its blending amount, the blending amount of any component of the raw material, the processing conditions (suction pressure, drying time, etc.) when manufacturing the adsorption filter, etc., its value can be controlled. In particular, as described in detail later, it is preferred to control the values ​​of pore volume with pore diameters greater than 10 μm, pore volume with pore diameters less than 7 μm, total pore volume and pore mode diameter by using two or more activated carbons with different physical properties as raw materials.

[0045] The density of the adsorption filter of the present embodiment (hereinafter also referred to simply as "filter density") is preferably 0.59 g / cm 3 By making the filter density at 0.59g / cm 3 The following can better maintain water resistance and is suitable for use in, for example, water purification filters. In addition, it can also suppress filter clogging. In addition, the filter density is preferably 0.35g / cm 3 By making the filter density at 0.35g / cm 3As described above, the total amount of activated carbon becomes an appropriate amount, and the removal performance of ultrafine particles and other common harmful substances can be kept good.

[0046] The filter density is more preferably 0.38 g / cm 3 More preferably, 0.40 g / cm 3 Above, particularly preferably 0.42 g / cm 3 By setting the filter density to 0.38 g / cm 3 The above results show that the adsorption filter has a more excellent chloroform (harmful substance) removal performance. In addition, the filter density is more preferably 0.57 g / cm 3 Below, more preferably 0.55 g / cm 3 Below, particularly preferably 0.53 g / cm 3 Hereinafter, in the present specification, the filter density can be measured by a method described in detail in the examples described later.

[0047] The filter density can be controlled by various methods. For example, the value can be controlled by appropriately selecting and appropriately adjusting the physical properties of the raw material activated carbon and its blending amount, the blending ratio of two or more activated carbons with different physical properties, the type and blending amount of the raw material binder, the blending amount of any component of the raw material, the processing conditions (suction pressure, drying time, etc.) when manufacturing the adsorption filter, etc. In particular, as described in detail later, it is preferred to control the filter density value by using two or more activated carbons with different physical properties as raw materials.

[0048] The benzene saturation adsorption capacity of the adsorption filter of the present embodiment is preferably 18% to 35%. In this specification, the benzene saturation adsorption capacity of the adsorption filter can be obtained by circulating air containing 1 / 10 of the solvent saturation concentration at 25°C and by using the sample weight gain (%) when the mass reaches a constant according to the activated carbon test method of JIS K 1474:2014.

[0049] By making the benzene saturated adsorption amount more than 18%, sufficient removal performance can be obtained, especially for organic matter. By making the benzene saturated adsorption amount less than 35%, it is possible to prevent the pore diameter from increasing in an overactivated state, and the possibility of reducing the adsorption and retention capacity of harmful substances can be suppressed. The benzene saturated adsorption amount is more preferably more than 20%, and more preferably more than 22%. In addition, the benzene saturated adsorption amount is more preferably less than 33%, and more preferably less than 30%.

[0050] The benzene saturation adsorption capacity of the adsorption filter of the present embodiment can be controlled by, for example, appropriately selecting and adjusting the physical properties of the raw material activated carbon and its blending amount, or the blending ratio of two or more activated carbons having different physical properties when using them.

[0051] Preferably, in the carbide obtained by heat treating the adsorption filter of the present embodiment at 900° C. for 20 minutes in an inert gas, specifically nitrogen gas (hereinafter also simply referred to as “heat treatment”), the content of particles having a particle size of 10 μm or less is 2% by volume or more.

[0052] Specifically, by subjecting the adsorption filter to the heat treatment, components such as the binder are removed from the adsorption filter, and the activated carbon in the adsorption filter remains as carbide. If the content of particles with a particle size of 10 μm or less in the particle size distribution of the remaining activated carbon in the adsorption filter (carbide after the heat treatment) is 2% by volume or more, the adsorption filter of the present embodiment before the heat treatment has a more excellent ultrafine particle removal performance.

[0053] The content of particles with a particle size of 10 μm or less in the activated carbon (carbide after heat treatment) in the adsorption filter is more preferably 4% by volume or more, and further preferably 6% by volume or more. There is no upper limit on the content of particles with a particle size of 10 μm or less in the activated carbon in the adsorption filter, as long as the particle size is not extremely small and does not significantly affect the water permeability of the adsorption filter of the present embodiment before heat treatment. For example, it can be 10% by volume or less.

[0054] The content of particles with a particle size of 10 μm or less of activated carbon (carbonized product after heat treatment) in the adsorption filter is a value that varies mainly depending on the physical properties of the raw activated carbon and the mixing ratio of two or more activated carbons with different physical properties. Therefore, its value can be controlled by appropriately selecting and adjusting them.

[0055] In addition, with respect to the adsorption filter of the present embodiment, it is preferred that the 0% particle size (hereinafter also referred to as "D0") in the cumulative particle size distribution based on volume of the activated carbon (carbide after heat treatment) in the adsorption filter is 7 μm or less. If D0 is 7 μm or less, the adsorption filter of the present embodiment before heat treatment has a more excellent ultrafine particle removal performance.

[0056] The D0 of the activated carbon (carbonized product after heat treatment) in the adsorption filter is more preferably less than 5 μm, and more preferably less than 3 μm. There is no lower limit for D0, as long as it does not significantly affect the water permeability of the adsorption filter before heat treatment. For example, it can be greater than 1 μm.

[0057] The D0 of the activated carbon (carbonized product after heat treatment) in the adsorption filter is also a value that varies mainly according to the physical properties of the raw activated carbon and the mixing ratio of two or more activated carbons with different physical properties when using them. Therefore, its value can be controlled by appropriately selecting and adjusting them.

[0058] In this specification, the content of particles with a particle size of less than 10 μm of the activated carbon (carbonized product after heat treatment) in the adsorption filter and the D0 of the activated carbon (carbonized product after heat treatment) in the adsorption filter are described in the embodiments described below. Like ordinary raw activated carbon, they can be measured by laser diffraction and scattering methods such as using a wet particle size distribution measuring apparatus ("Microtrac MT3300EX-II" manufactured by MicrotracBEL).

[0059] [Structure of adsorption filter]

[0060] The adsorption filter of the present embodiment includes a molded body containing activated carbon and a binder.

[0061] (Activated carbon)

[0062] The raw material activated carbon (preferably granular activated carbon) used in the adsorption filter of the present embodiment is not particularly limited, and it may be used alone or in combination of two or more kinds of activated carbons having different physical properties.

[0063] The physical properties of raw activated carbon include, for example, the packing density (g / cm 3 ), the 10% particle size in the cumulative particle size distribution based on volume (hereinafter also referred to as "D10"), the 50% particle size in the cumulative particle size distribution based on volume (hereinafter also referred to as "D50"), the 90% particle size in the cumulative particle size distribution based on volume (hereinafter also referred to as "D90"), etc.

[0064] In the present embodiment, it is preferred to use two or more activated carbons with different physical properties in combination. This is because: by adjusting the mixing ratio of activated carbons with different physical properties, when forming the adsorption filter, its voids can be controlled and the pore volume with a pore diameter of 10 μm or more (and / or the pore volume with a pore diameter of 7 μm or less and the total pore volume) can be easily adjusted to be within the specific range specified in the present embodiment.

[0065] As activated carbons with different physical properties, it is preferred to use a powdered activated carbon X having a smaller D10, D50 and / or D90 and containing more fine powders and a powdered activated carbon Y having a larger D10, D50 and / or D90 in combination. When the activated carbon X and activated carbon Y are used in combination, the activated carbon Y is combined with the activated carbon X at a mass ratio greater than the same degree, so that when the adsorption filter is molded, the excessive voids formed by the activated carbon Y are appropriately filled with the fine powder of the activated carbon X. As a result, the voids of the molded body are appropriately controlled, and the pore volume with a pore diameter of 10 μm or more (and / or the pore volume with a pore diameter of 7 μm or less and the total pore volume) is adjusted within the specific range specified in this embodiment.

[0066] The particle size distribution of the raw activated carbon is not particularly limited, but preferably the particle content of particles with a particle size of 10 μm or less exceeds 2% by volume. Specifically, in the particle size distribution of the raw activated carbon, by making the particle content of particles with a particle size of 10 μm or less exceed 2% by volume, the fine powder contained in the activated carbon in the adsorption filter becomes more, and the filter shows a more excellent ultrafine particle removal performance. The particle content of the raw activated carbon with a particle size of 10 μm or less changes according to the physical properties of each activated carbon and the proportion of each activated carbon when two or more activated carbons are used in combination. Therefore, by appropriately selecting and appropriately adjusting them, it is possible to control its value.

[0067] The content of particles with a particle size of 10 μm or less in the raw activated carbon is more preferably 3% by volume or more, further preferably 4% by volume or more, and further preferably 5% by volume or more. There is no upper limit on the content of particles with a particle size of 10 μm or less in the raw activated carbon, as long as the water permeability of the formed adsorption filter is not significantly affected by the excessive fine powder contained in the activated carbon in the adsorption filter. For example, it can be 15% by volume or less.

[0068] In this specification, the packing density, D10, D50 and D90 of the raw activated carbon can be controlled by, for example, appropriately selecting and appropriately adjusting the type of carbonaceous material that becomes the raw material of the activated carbon and the activation treatment method and treatment conditions (heating temperature and time, etc.), pulverization conditions and classification conditions of the carbonaceous material when manufacturing the activated carbon. In addition, D10, D50 and D90 and the content of particles with a particle size of less than 10 μm of the raw activated carbon can be measured, for example, by laser diffraction and scattering methods using a wet particle size distribution measuring device ("Microtrac MT3300EX-II" manufactured by Microtrac Bair) as described in the examples described below.

[0069] As the raw material activated carbon, a commercially available product may be used. Alternatively, for example, activated carbon obtained by, as required, carbonizing a carbonaceous material to be a raw material of activated carbon, activating it, and, as required, washing it, drying it, and pulverizing it may be used.

[0070] The carbonaceous material as a raw material is not particularly limited, and examples thereof include: plant-based carbonaceous materials (e.g., wood, wood shavings, charcoal, fruit shells such as coconut shells and walnut shells, fruit seeds, byproducts of pulp manufacturing, lignin, waste molasses and other plant-based materials); mineral-based carbonaceous materials (e.g., peat, lignite, brown coal, bituminous coal, anthracite, coke, coal tar, coal tar, petroleum distillation residues, petroleum asphalt and other mineral-based materials); synthetic resin-based carbonaceous materials (e.g., phenolic resin, polyvinylidene chloride, acrylic resin and other synthetic resin-based materials); natural fiber-based carbonaceous materials (e.g., natural fiber such as cellulose, natural fiber such as regenerated fiber such as rayon and other natural fiber-based materials), etc. These carbonaceous materials can be used alone or in combination of two or more.

[0071] Among these carbonaceous materials, coconut shell or phenolic resin is preferred from the viewpoint of easily developing micron-order pores which are related to the volatile organic compound removal performance specified in JIS S 3201:2019.

[0072] When carbonization treatment is required, the carbonaceous materials can be carbonized in an environment that is generally isolated from oxygen or air at, for example, 400 to 800° C., preferably 500 to 800° C., and more preferably 550 to 750° C. The particle size can be adjusted as needed.

[0073] Then, the carbonaceous material is subjected to activation treatment. Activation treatment is a treatment for forming pores on the surface of the carbonaceous material to convert it into a porous activated carbon. The activation treatment can be carried out using a general method in the technical field, without particular limitation, and mainly includes two treatment methods: gas activation treatment and chemical reagent activation treatment. Among them, when used for water purification, gas activation treatment is preferred from the viewpoint of less residual impurities.

[0074] Gas activation treatment is a treatment in which a carbonaceous material is heated in the presence of, for example, water vapor, carbon dioxide, air, oxygen, combustion gas or a mixture thereof. The heating temperature is not particularly limited, and is carried out at a temperature of, for example, 700°C to 1100°C, preferably 800°C to 980°C, and more preferably about 850°C to 950°C. The activation time and the heating rate are not particularly limited, and can be appropriately adjusted according to the type, shape and size of the selected carbonaceous material. Considering safety and reactivity, it is preferably carried out using a water vapor-containing gas containing 10% to 40% by volume of water vapor. The chemical reagent activation treatment is carried out by a known method in which an activator such as zinc chloride, calcium chloride, phosphoric acid, sulfuric acid, sodium hydroxide, potassium hydroxide, magnesium hydroxide, calcium hydroxide, etc. is mixed with a carbonaceous material and heated under an inert gas atmosphere.

[0075] The activated carbon after the activation treatment is washed and dried as needed. Specifically, when plant-based carbonaceous materials such as coconut shells or mineral-based carbonaceous materials containing impurities such as alkali metals, alkaline earth metals and transition metals are used as raw materials for activated carbon, washing is performed as needed to remove ash or chemical reagents. Inorganic acid or water is used for washing, and hydrochloric acid with high washing efficiency is preferred as the inorganic acid.

[0076] The activated carbon after the activation treatment is subjected to pulverization and / or classification as needed. The pulverization can be carried out using a pulverizing device commonly used for pulverizing activated carbon, such as an air-fall autogenous mill, a rod mill, a roller mill, a hammer mill, a blade grinder, a pin mill, and other high-speed rotary mills, a ball mill, a jet mill, and the like. The classification treatment can include methods commonly used for the classification of activated carbon, such as classification using a sieve, wet classification, and dry classification. Wet classifiers can include classifiers that use principles such as gravity classification, inertial classification, hydraulic classification, and centrifugal classification. Dry classifiers can include classifiers that use principles such as sedimentation classification, mechanical classification, and centrifugal classification.

[0077] The activated carbon obtained by the treatment or commercially available activated carbon may be in any form such as powder, granules, fibers (filaments, woven fabrics, felts), etc., and may be appropriately selected according to the application. Among these forms, a powder having high adsorption performance per unit volume is preferred.

[0078] (Binder)

[0079] The binder used in the adsorption filter of the present embodiment is not particularly limited, and a powdery or fibrous binder may be used alone or in combination of two or more. Of these, a fibrous binder is preferably included from the viewpoint of excellent water permeability when molding the adsorption filter.

[0080] As a fibrous binder, there is no particular limitation as long as it can wrap around activated carbon and give a shape, and both synthetic and natural products can be widely used. As such a binder, for example, acrylic fiber, polyethylene fiber, polypropylene fiber, polyacrylonitrile fiber, cellulose fiber, nylon fiber, aramid fiber, pulp, etc. can be cited. The fiber length of the fibrous binder is preferably 4 mm or less.

[0081] The fibrous binder preferably includes an acrylic fibrous binder. In addition, the fibrous binder preferably includes a cellulose fibrous binder. In addition, these fibrous binders can be used in combination of two or more. For example, it is more preferred to use both an acrylic fibrous binder and a cellulose fibrous binder in combination. By using a cellulose fibrous binder in combination, the fine powder flowing out of the adsorption filter of the present embodiment can be reduced. Regarding the mixing ratio of the acrylic fibrous binder and the cellulose fibrous binder, the cellulose fibrous binder is preferably 30 to 70 parts by mass, and more preferably 40 to 60 parts by mass, relative to 100 parts by mass of the acrylic fibrous binder.

[0082] In the present embodiment, the water permeability of the fibrous binder is preferably about 1 mL to 200 mL in terms of CSF value. In addition, the CSF value is more preferably 10 mL to 150 mL. Here, in this specification, the CSF value is a value measured by the Canadian Standard Freeness Method, "Test Method for Freeness of Pulp" specified in JIS P 8121:2012. Specifically, it is a value evaluated using tap water with a conductivity of about 100 μs / cm in the measurement. It should be noted that the CSF value can be adjusted, for example, by fibrillating the binder.

[0083] By making the CSF value of the fibrous binder 1 mL or more, it is possible to maintain sufficient water permeability, suppress the strength reduction of the molded body, and prevent the possibility of pressure loss. In addition, by making the CSF value 200 mL or less, the powdered activated carbon can be fully maintained, and the strength reduction of the molded body can be suppressed, and the possibility of adsorption performance reduction can be prevented. It should be noted that when two or more fibrous binders are used in combination, it is preferred that the CSF value of the two or more fibrous binders in the mixed state meets the above range.

[0084] Specifically, when the fibrous binder includes an acrylic fibrous binder, the CSF value of the acrylic fibrous binder is preferably 20 mL or more, more preferably 50 mL or more. In addition, the CSF value of the acrylic fibrous binder is preferably 200 mL or less, more preferably 150 mL or less. By setting it within this range, even if the fibrous binder includes other fibrous binders other than the acrylic fibrous binder, the CSF value of the fibrous binder as a whole including the acrylic fibrous binder becomes an appropriate value, which can improve the strength of the molded body, reduce pressure loss, maintain powdered activated carbon, and maintain adsorption performance. In addition, from the same point of view, when the fibrous binder includes an acrylic fibrous binder and a cellulose fibrous binder, the cellulose fibrous binder is preferably: the CSF value in the state of mixing 50 parts by mass of the cellulose fibrous binder with 100 parts by mass of the acrylic fibrous binder is 1 mL or more, more preferably 10 mL or more. The CSF value of the cellulose-based fibrous binder in a state where 50 parts by mass of the cellulose-based fibrous binder is mixed with 100 parts by mass of the acrylic-based fibrous binder is preferably 50 mL or less, more preferably 40 mL or less.

[0085] The mixing ratio of activated carbon and binder is not particularly limited, and is appropriately set to: after the adsorption filter is formed, the pore volume with a pore diameter of 10 μm or more (and / or the pore volume with a pore diameter of 7 μm or less and the total pore volume) is within the specific range specified in the present embodiment. For example, considering the adsorption performance of the activated carbon and the formability of the adsorption filter, the binder is preferably about 3 to 8 parts by mass relative to 100 parts by mass of the activated carbon. By setting the amount of the binder to more than 3 parts by mass, a molded body of the adsorption filter with sufficient strength can be obtained. By setting the amount of the binder to less than 8 parts by mass, the reduction in the adsorption performance of the activated carbon in the adsorption filter can be suppressed.

[0086] The mixing ratio of the binder to 100 parts by mass of the activated carbon is more preferably 4 parts by mass or more, and further preferably 5 parts by mass or more. In addition, the mixing ratio of the binder to 100 parts by mass of the activated carbon is more preferably 7 parts by mass or less, and further preferably 6 parts by mass or less.

[0087] (Optional ingredient)

[0088] In addition, as long as the effect of the present invention is not hindered, the adsorption filter of the present embodiment may also contain other arbitrary functional components. Examples include zeolite powder (lead adsorbent), ion exchange resin or chelate resin that can adsorb and remove soluble lead. In addition, in order to impart antibacterial properties, various adsorbents containing silver ions or silver compounds may be included alone, or two or more may be contained in combination. As an example of the adsorbent, silver-loaded activated carbon added in an amount that does not affect the physical properties of the adsorption filter of the present embodiment may be cited. The amount of these other arbitrary components is not particularly limited, and is appropriately set to: after the adsorption filter is formed, the pore volume with a pore diameter of 10 μm or more (and / or the pore volume with a pore diameter of 7 μm or less and the total pore volume) is within the specific range specified in the present embodiment. For example, 1 to 20 parts by mass can be added relative to 100 parts by mass of the adsorption filter as a whole.

[0089] The adsorption filter of the molded body including activated carbon and a binder of the present embodiment may further include a core, or may be a cylindrical adsorption filter. By setting it to a cylindrical shape, the water flow resistance can be reduced. In addition, when it is filled into a housing and used as a filter element as described later, it has the advantage of being able to simply load the filter element into a water purifier and simply perform replacement operations.

[0090] The core is not particularly limited as long as it can be inserted into the hollow part of the cylindrical adsorption filter to reinforce the cylindrical adsorption filter. Examples thereof include a trical pipe, a net pipe, a ceramic filter, etc. In addition, a nonwoven fabric may be wrapped around the periphery of the core for use.

[0091] [Method for manufacturing adsorption filter]

[0092] The method for producing the adsorption filter of the present embodiment may be carried out by any method known to those skilled in the art, and is not particularly limited. From the viewpoint of enabling efficient production, a slurry suction method is preferred.

[0093] Hereinafter, an example of a method for producing the cylindrical adsorption filter according to the present embodiment will be described in detail, but the present invention is not limited to this production method.

[0094] Specifically, for example, the cylindrical adsorption filter (molded body) of the present embodiment can be manufactured by a method including a slurry preparation process, a suction filtration process, a rotation process performed as needed, a drying process, and a grinding process performed as needed. In the slurry preparation process, powdered activated carbon and a fibrous binder are dispersed in water to prepare a slurry. In the suction filtration process, the prepared slurry is filtered while suctioning to obtain a preformed body. In the rotation process, the shape of the outer surface is adjusted as needed by compressing the preformed body after suction filtration on a shaping table. In the drying process, the preformed body after the shape is dried to obtain a dried molded body. In the grinding process, the outer surface of the dried molded body is ground as needed. Below, each process is described in more detail.

[0095] (Slurry preparation process)

[0096] In the slurry preparation process, for example, a slurry in which powdered activated carbon and a fibrous binder are dispersed in a solvent is prepared in such a manner that the fibrous binder is 4 to 8 parts by mass relative to 100 parts by mass of powdered activated carbon, and the solid content concentration is 0.1% to 10% by mass, preferably 1% to 5% by mass. The solvent is not particularly limited, and water or the like is preferably used. By adjusting the solid content concentration of the slurry to a concentration that is not too high, it is easy to make the dispersion uniform, and unevenness of the molded body can be prevented. On the other hand, by adjusting the solid content concentration of the slurry to a concentration that is not too low, the molding time can be shortened, and productivity can be improved. In addition, the situation where the density of the molded body becomes too high is suppressed, and good water permeability can be maintained.

[0097] (Filtration process)

[0098] use Figure 1 The filtration process is described. Figure 1 In the figure, each reference numeral represents: template 1, core 2, suction hole 3, flange 4, 4' and filtrate outlet 5. In the suction filtration process, for example, Figure 1 The cylindrical molded body template 1 shown in the figure has a plurality of suction holes 3 on the surface of the core body 2, flanges 4, 4' are installed at both ends, and a filtrate discharge port 5 is provided. First, the core as described above is installed in the template 1, and the prepared slurry is placed, and the slurry is filtered while suctioning from the inner side of the template 1 through the filtrate discharge port 5, so that the slurry is attached to the template 1. As a suction method, a conventional method can be used, such as a method of suction using a suction pump, etc. In this way, the preform is attached to the template 1.

[0099] (Rotation process)

[0100] According to the need, a rotation process can be performed after the filtration process to adjust the outer diameter of the preform to a specified size, improve the roundness, and reduce the unevenness of the outer peripheral surface. In the rotation process, the template 1 in the state of the preform obtained in the filtration process being attached is placed on a table, and it can be moved forward and backward while being pressed with a specified force.

[0101] In order to obtain a desired pore volume and density of the adsorption filter, etc., the suction filtration step and the rotation step performed as required may be performed any number of times.

[0102] (Drying process)

[0103] Next, the flanges 4 and 4' at both ends of the template 1 are removed to pull out the core 2. Thus, a hollow cylindrical preform can be obtained. In the drying step, the preform removed from the template 1 as described above is dried using a dryer or the like to obtain a hollow cylindrical preform. Figure 2 The molded body 6 shown (adsorption filter of this embodiment).

[0104] The drying temperature is, for example, 100° C. to 150° C., particularly about 110° C. to 130° C. The drying time is, for example, 4 to 24 hours, particularly about 8 to 16 hours. By setting the drying temperature not too high, it is possible to prevent the occurrence of a decrease in filtration performance or a decrease in strength of the molded body due to deterioration or melting of the fibrous binder. By setting the drying temperature not too low, the drying time can be shortened, and insufficient drying can be prevented.

[0105] (Grinding process)

[0106] If necessary, a grinding process can be performed after the drying process to further adjust the outer diameter of the adsorption filter or reduce the unevenness of the outer peripheral surface. The grinding method is not particularly limited as long as the outer surface of the dried molded body can be ground (or polished), and any grinding method known to those skilled in the art can be used. From the viewpoint of uniformity of grinding, it is preferred to use a method of grinding a grinder that rotates the molded body itself for grinding.

[0107] It should be noted that the grinding process is not limited to the method using a grinder, and for example, a fixed flat grinding stone can be used to grind the molded body fixed to the rotating shaft. In this method, the generated grinding chips are easily accumulated on the grinding surface, so it is effective to perform grinding while blowing air.

[0108] [Applications of adsorption filters, etc.]

[0109] The adsorption filter of this embodiment can be used as, for example, a water purification filter, an artificial dialysis filter, etc. When used as a water purification filter or an artificial dialysis filter, for example, the adsorption filter is manufactured using the above-mentioned manufacturing method, shaped and dried, and then cut into a desired size and shape, and then used as a filter. Moreover, a cover can be installed on the front end portion or a non-woven fabric can be installed on the surface as needed.

[0110] The adsorption filter of this embodiment can be filled into a housing and used as a water purification filter element. The water purification filter element is loaded into a water purifier and used for water circulation. As the water circulation method, a full filtration method or a circulation filtration method for filtering the total amount of raw water can be adopted. The water purification filter element loaded into the water purifier, for example, can be used by filling the water purification filter (the adsorption filter of this embodiment) into the housing. Alternatively, the water purification filter can also be further used in combination with a known non-woven filter, various adsorbents, mineral additives, ceramic filter materials, etc.

[0111] The outline of the present invention has been described above, and the adsorption filter of the present embodiment is summarized as follows.

[0112] An adsorption filter according to one aspect of the present invention is an adsorption filter comprising a molded body containing activated carbon and a binder, wherein the adsorption filter has a volume-based pore volume of 0.10 cm-1 or more of pores having a diameter of 10 μm or more measured by mercury intrusion porosimetry. 3 / cc~0.39cm 3 / cc.

[0113] In the adsorption filter, preferably: the density of the adsorption filter is 0.59 g / cm 3 the following.

[0114] In the above-mentioned adsorption filter, it is more preferred that the total pore volume of the adsorption filter measured by mercury intrusion porosimetry is 0.50 cm 3 / cc~0.73cm 3 / cc.

[0115] In the above adsorption filter, it is further preferred that the ratio of the volume-based pore volume of the adsorption filter having a pore diameter of 10 μm or more measured by mercury intrusion porosimetry to the volume-based total pore volume of the adsorption filter measured by mercury intrusion porosimetry is 12% or more.

[0116] In the above-mentioned adsorption filter, it is particularly preferred that the pore volume of the adsorption filter with a volume-based pore diameter of 7 μm or less measured by mercury intrusion porosimetry is 0.15 cm 3 / cc and above.

[0117] In the adsorption filter, it is more preferred that the ratio of the volume-based pore volume of the adsorption filter having a pore diameter of 7 μm or less measured by mercury intrusion porosimetry to the volume-based total pore volume of the adsorption filter measured by mercury intrusion porosimetry is 22% or more.

[0118] Alternatively, another aspect of the present invention is an adsorption filter comprising a molded body containing activated carbon and a binder, wherein the adsorption filter has a volume-based pore volume of 0.15 cm-1 with a pore diameter of 7 μm or less as measured by mercury intrusion porosimetry. 3 / cc or more, and the total pore volume of the adsorption filter measured by mercury intrusion porosimetry is 0.50 cm 3 / cc~0.73cm 3 / cc.

[0119] In the above adsorption filter, preferably, the ratio of the volume-based pore volume of the adsorption filter having a pore diameter of 7 μm or less measured by mercury intrusion porosimetry to the volume-based total pore volume of the adsorption filter measured by mercury intrusion porosimetry is 22% or more.

[0120] In the above-mentioned adsorption filter, it is more preferred that the pore mode diameter measured by mercury intrusion porosimetry is 15 μm or less.

[0121] In the above adsorption filter, it is further preferred that the content of particles having a particle size of 10 μm or less in the carbide obtained by heat treating the adsorption filter at 900° C. for 20 minutes in an inert gas is 2% by volume or more.

[0122] In the adsorption filter, it is particularly preferred that the benzene saturation adsorption amount is 18% to 35%, and the benzene saturation adsorption amount is obtained by circulating air containing solvent vapor of 1 / 10 of the saturation concentration of the solvent at 25°C and from the weight increase of the sample when the mass reaches a constant.

[0123] In the above adsorption filter, preferably, in a carbide obtained by heat treating the adsorption filter at 900° C. for 20 minutes in an inert gas, a 0% particle size in a volume-based cumulative particle size distribution is 7 μm or less.

[0124] In the adsorption filter, it is more preferred that the binder comprises a fibrous binder.

[0125] In the adsorption filter, it is further preferred that the fibrous binder includes an acrylic fibrous binder.

[0126] In the adsorption filter, it is particularly preferred that the fibrous binder includes a cellulose-based fibrous binder.

[0127] Example

[0128] Hereinafter, the present invention will be further specifically described by way of examples, but the present invention is not limited to these examples in any way.

[0129] First, the details of the raw materials used in the examples and comparative examples, the methods for measuring the physical properties of the raw material powdered activated carbon, and the methods for measuring the physical properties and the evaluation methods of the produced adsorption filters are described.

[0130] [Raw materials for adsorption filters]

[0131] (Powdered activated carbon and fibrous activated carbon)

[0132] Hereinafter, a method for producing powdered activated carbon and fibrous activated carbon used as raw materials will be described, but the production method is not particularly limited as long as the necessary physical properties are satisfied.

[0133] Powdered activated carbon A

[0134] Coconut shell charcoal obtained by carbonizing coconut shells produced in the Philippines was steam activated at 900°C, the activation time was adjusted to achieve the target benzene adsorption amount, the coconut shell activated carbon obtained was washed with dilute hydrochloric acid, and desalted with ion exchange water, thereby obtaining granular activated carbon (JIS K 1474, 18×42 mesh, benzene adsorption amount 29.5wt%). The obtained granular activated carbon was crushed with a ball mill to obtain powdered activated carbon A with a D50 of 19.5μm.

[0135] Powdered activated carbon B

[0136] The coconut shell charcoal obtained by carbonizing coconut shells produced in the Philippines was steam activated at 900°C, the activation time was adjusted to achieve the target benzene adsorption amount, the coconut shell activated carbon was washed with dilute hydrochloric acid, and desalted with ion exchange water, thereby obtaining granular activated carbon (JIS K 1474, 18×42 mesh, benzene adsorption amount 30.1wt%). The obtained granular activated carbon was crushed with a ball mill, and the fine powder was removed using a dry classifier to obtain a powdered activated carbon B with a D50 of 36.8μm.

[0137] Powdered activated carbon C

[0138] The coconut shell charcoal obtained by carbonizing coconut shells produced in the Philippines was steam activated at 900°C, the activation time was adjusted to achieve the target benzene adsorption amount, the coconut shell activated carbon was washed with dilute hydrochloric acid, and desalted with ion exchange water, thereby obtaining granular activated carbon (JIS K 1474, 18×42 mesh, benzene adsorption amount 27.9wt%). The obtained granular activated carbon was crushed with a ball mill, and the fine powder was removed using a dry classifier to obtain a powdered activated carbon C with a D50 of 33.2μm.

[0139] Powdered activated carbon D

[0140] The coconut shell carbon obtained by carbonizing coconut shells produced in the Philippines was activated by steam at 900°C, and the activation time was adjusted to achieve the target benzene adsorption amount. The coconut shell activated carbon obtained was washed with dilute hydrochloric acid and desalted with ion exchange water, thereby obtaining granular activated carbon (JIS K 1474, 18×42 mesh, benzene adsorption amount 29.7wt%). The obtained granular activated carbon was crushed with a ball mill and then classified with a 325-mesh sieve to obtain powdered activated carbon D with a D50 of 145.3μm.

[0141] Powdered activated carbon E

[0142] Bituminous coal was used as a carbonaceous raw material and carbonized at 650°C to obtain a carbonized product. The obtained carbonized product was put into a furnace, and the activation time was adjusted in a manner to achieve the target benzene adsorption amount. The obtained coal-based activated carbon was washed with dilute hydrochloric acid and desalted with ion exchange water, thereby obtaining acid-washed activated carbon. The obtained acid-washed activated carbon was put into a furnace again, and the activation time was adjusted in a manner to achieve the target benzene adsorption amount to obtain granular activated carbon (JIS K 1474, 10×32 mesh, benzene adsorption 42.1wt%). The obtained granular activated carbon was crushed with a ball mill to obtain powdered activated carbon E with a D50 of 36.8μm.

[0143] The detailed physical properties of powdered activated carbon A to powdered activated carbon E are shown in Table 1 below.

[0144] Table 1

[0145]

[0146] Fibrous activated carbon

[0147] The phenolic resin fiber was oxidized at 300°C for 1 hour, and the oxidized product was carbonized at 700°C for 1 hour. The carbonized phenolic resin fiber was activated at 950°C to obtain a BET specific surface area of ​​1850 m 2 / g of phenolic resin fibrous activated carbon.

[0148] (Binder)

[0149] Acrylic fiber binder: manufactured by Japan Exlan Industries, Ltd., "Acrylic fiber Bi-PUL / F", CSF value 83ml

[0150] Cellulose-based fibrous binder (CSF value was 28 mL in a state where 50 parts by mass of the cellulose-based fibrous binder was blended with 100 parts by mass of the acrylic-based fibrous binder (CSF value: 83 mL)).

[0151] Powder binder (high-density polyethylene powder binder): Mitsui Chemicals, Inc., "MIPELON MX-220"

[0152] (other)

[0153] Titanosilicate lead adsorbent: Solenis, "ATS", average particle size 20 μm

[0154] Core: Made by Yamatobo Progress Co., Ltd., "PMF-30CS-30-33"

[0155] Nonwoven fabric: Made by Shinwa Co., Ltd., "9540-F"

[0156] [Measurement of particle size distribution of raw activated carbon]

[0157] The D10 (μm), D50 (μm), D90 (μm), and the content of particles with a particle size of less than 10 μm (volume %) of the raw activated carbon were measured by laser diffraction and scattering. That is, the activated carbon to be measured was added to ion exchange water together with a surfactant, ultrasonic vibration was applied to prepare a uniform dispersion, and the wet particle size distribution measuring device (manufactured by Microtrac MT3300EX-II) was used for measurement. The surfactant used was "Polyoxyethylene (10) octylphenyl ether" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. The analysis conditions are shown below.

[0158] (Analysis conditions)

[0159] Number of measurements: average of 3 times

[0160] Measurement time: 30 seconds

[0161] Distribution display; volume

[0162] Particle size classification; Standard

[0163] Calculation mode; MT3000II

[0164] Solvent name: Water

[0165] Upper limit of measurement: 2000μm, lower limit of measurement: 0.021μm

[0166] Residual component ratio; 0.00

[0167] By composition ratio; 0.00

[0168] Residual component ratio setting; invalid

[0169] Particle permeability; absorption

[0170] Particle refractive index; not applicable (N / A)

[0171] Particle shape: Not applicable (N / A)

[0172] Solvent refractive index: 1.333

[0173] DV value: 0.0882

[0174] Transmittance (TR): 0.880~0.900

[0175] Dilation filter; invalid

[0176] Flow rate: 70%

[0177] Ultrasonic output: 40W

[0178] Ultrasonic time: 180 seconds

[0179] [Determination of adsorption filter density]

[0180] The obtained adsorption filter was dried at 120°C for 2 hours, and the density of the adsorption filter (g / cm 3 ). It should be noted that the adsorption filter density refers to the density of the activated carbon molding layer itself.

[0181] Adsorption filter density = (mass of the activated carbon molded layer of the adsorption filter) / (volume of the activated carbon molded layer of the adsorption filter)

[0182] [Measurement of pore volume and pore mode diameter of adsorption filter using mercury porosimetry]

[0183] The pore volume of the adsorption filter was measured using a mercury intrusion pore volume measuring device (manufactured by Micromeritics, "MicroActive AutoPoreV 9620"). The measuring pressure was set to 0.7 kPa-420 MPa. Figure 3 After cutting the molded layer of the cylindrical adsorption filter containing activated carbon and a binder, the cut slices were further cut into approximately 1 cm squares. The pore volume (cm2) of the adsorption filter with a pore diameter of 10 μm or more based on the weight was calculated for the approximately 1 cm square sample. 3 / g), pore volume (cm2) with pore diameter of 7 μm or less 3 / g) and total pore volume (cm 3Then, these values ​​were multiplied by the above-determined density of the adsorption filter to calculate the volume-based pore volume (cm2) of the adsorption filter with a pore diameter of 10 μm or more. 3 / cc), pore volume with pore diameter of 7 μm or less (cm 3 / cc) and total pore volume (cm 3 In addition, based on the calculated pore volume values, the pore volume (cm2) of pores with a diameter of 10 μm or more was determined. 3 / cc) relative to the total pore volume (cm 3 / cc) ratio (%) and pore volume (cm 3 / cc) relative to the total pore volume (cm 3 In addition, the pore mode diameter (μm) of the adsorption filter was defined as the pore diameter showing the peak value of the obtained pore distribution.

[0184] [Measurement of particle size distribution of activated carbon (carbonized product after heat treatment) in adsorption filter]

[0185] The adsorption filter manufactured in each of the embodiments and comparative examples described below and before the peripheral nonwoven fabric and the gasket are installed is shaped like this from the end surface in the long axis direction. Figure 4 As shown, use a cutter to make the volume about 6cm 3 The cut sample is randomly cut as a sample in a manner. The cut sample is placed in a crucible, heat treated in a nitrogen atmosphere at 900°C for 20 minutes, and then cooled to room temperature in a nitrogen atmosphere. The obtained carbide is used as a sample for measuring the particle size distribution of activated carbon in the adsorption filter. The same method as the above-mentioned particle size distribution measurement method of the raw activated carbon is used to measure the 0% particle size (D0) (μm) and the content of particles with a particle size of less than 10μm in the volume-based cumulative particle size distribution of the activated carbon in the adsorption filter (volume %).

[0186] [Measurement of benzene adsorption performance of adsorption filter]

[0187] Regarding the benzene adsorption performance of the adsorption filter, the activated carbon test method in Japanese Industrial Standards (JIS K1474: 1991) was used as a reference, and the benzene saturated adsorption amount (%) was calculated from the weight increase of the sample when the mass reached a constant when air containing solvent vapor at 1 / 10 of the saturated concentration of the solvent was circulated at 25°C. As the measurement sample, a part of the adsorption filter was cut and crushed, and the adsorption performance of the crushed sample was evaluated.

[0188] [Ultrafine particle removal performance measurement]

[0189] Fluoro-Max (trademark) Green Fluorescent Polymer Microspheres G500 (particle diameter 0.5 μm) manufactured by Thermo Fisher Scientific was used, and the dilution water with a concentration of 10,000 particles / ml or more was adjusted to a water temperature of 20±3°C as test water. The test water was circulated from the outside to the inside of the cylindrical adsorption filter at a flow rate of 2.85 L / min, and the test water and the treated water were extracted simultaneously as time went by to form the sample water. The test water was filtered with a 0.2 μm membrane filter (manufactured by ADVANTEC, membrane filter A020B025A white (cellulose mixed ester, 0.2 μm, 25 mm, with black grid lines) and the membrane filter was dried at 60°C. The number of fluorescent particles in the two sample waters was calculated by fixing the dried membrane filter on a slide and observing it with a fluorescence microscope ("BX51-34-FL" manufactured by Olympus Corporation), and the removal rate (%) of the particles contained in the test water was calculated. In this removal performance test, the removal rate of fluorescent particles when 10940L of water was circulated was evaluated, and a removal rate of 95% or more was used as a qualified standard for ultrafine particle removal performance.

[0190] [Initial water flow resistance measurement]

[0191] Water at 20±3°C was passed from the outside to the inside of the cylindrical adsorption filter at a flow rate of 2.85 L / min, and the water flow resistance (MPa) was measured 10 minutes after the water flow began. In this test, an initial water flow resistance of 0.2 MPa or less was considered acceptable. In addition, the water flow resistance value does not include the shell resistance.

[0192] [Chloroform (harmful substance) removal performance measurement]

[0193] Test water with a chloroform concentration of 300 ppb was passed from the outside to the inside of the cylindrical adsorption filter at a flow rate of 2.85 L / min at 20±2.5°C. The cumulative water flow (L) when the chloroform removal rate was less than 95% was evaluated as the chloroform removal performance.

[0194] [Determination of water permeability of micro powder]

[0195] Water was passed through a cylindrical adsorption filter at a flow rate of 2.85 L / min to extract 100 ml of outflow water immediately after the water was passed. The absorbance of the outflow water after extraction was measured using an ultraviolet visible spectrophotometer (manufactured by Shimadzu Corporation, "UV-1800"), and the amount of fine powder in the outflow water was obtained from a pre-made calibration curve.

[0196] Next, the method for producing the adsorption filter of each example and each comparative example, and the results of measuring the physical properties and evaluating the performance of the produced adsorption filter will be described in detail.

[0197] <Example 1>

[0198] Powdered activated carbon A, powdered activated carbon B, acrylic fibrous binder, cellulose fibrous binder, and titanosilicate lead adsorbent were prepared in a total of 1.055 kg in the proportion shown in Table 2, and tap water was added. The amount of slurry after addition was 20 L. It should be noted that Table 2 also records the particle content (volume %) of the raw material activated carbon with a particle size of less than 10 μm measured by the above method.

[0199] Next, install the core in the above Figure 1 The cylindrical molding die shown in FIG. 1 (outer diameter 60 mmφ, center axis diameter 30 mmφ, and outer diameter flange interval 84.9 mmH) was molded by suctioning the obtained slurry at 450 mmHg until it reached 62 mmφ, which was slightly larger than the outer diameter of the mold, and then dried. Figure 5 The automatic grinding machine shown grinds the outer surface of the molded body under the conditions of 360 rotations / min of the molded body, 2535 rotations / min of the grindstone, and 300 mm / 10 sec (3 cm / sec) of the grindstone movement, thereby obtaining a cylindrical adsorption filter with an outer diameter of 60 mmφ, an inner diameter of 30 mmφ, and a height of 84.9 mmH.

[0200] The density of the adsorption filter obtained as described above, the pore volume and pore mode diameter obtained by mercury porosimetry, the particle size distribution of the activated carbon (carbonized product after heat treatment) in the adsorption filter, and the benzene adsorption performance were measured by the above-mentioned method. The results of the physical property measurements of the adsorption filter are summarized in Table 3 described below.

[0201] Then, a layer of nonwoven fabric was wrapped around the outer circumference of the obtained adsorption filter. Furthermore, gaskets punched out in a donut shape with an outer diameter of 60 mmφ and an inner diameter of 30 mmφ formed from a 2 mm thick foamed polyethylene sheet were bonded to both ends of the adsorption filter using a hot melt adhesive.

[0202] The adsorption filter with nonwoven fabric wrapped and gasket bonded was installed in a container with an average diameter of 96 mm, a length of about 240 mm, and an internal volume of about 1809 cm 3 The water was passed from the outside to the inside of the stainless steel housing. The ultrafine particle removal performance, initial water flow resistance, chloroform (harmful substance) removal performance and water flow fine powder amount were evaluated by the above method. These performance evaluation results are also summarized in Table 3 described later.

[0203] <Example 2>

[0204] As shown in Table 2 described below, in Example 2, a cylindrical adsorption filter was obtained by the same method as in Example 1 except that the cellulose-based fibrous binder was not added to the raw material. The results of the physical property measurement and performance evaluation of the adsorption filter in Example 2 are summarized in Table 3 described below.

[0205] <Example 3>

[0206] As shown in Table 2 described below, in Example 3, the amount of powdered activated carbon A was slightly increased and the amount of powdered activated carbon B was slightly reduced compared to Example 1, and a cylindrical adsorption filter was obtained by the same method as in Example 1. The results of the physical property measurement and performance evaluation of the adsorption filter in Example 3 are summarized in Table 3 described below.

[0207] <Example 4>

[0208] As shown in Table 2 described below, in Example 4, the amount of powdered activated carbon A was further increased and the amount of powdered activated carbon B was further reduced compared to Example 3, and a cylindrical adsorption filter was obtained by the same method as in Example 3. The results of the physical property measurement and performance evaluation of the adsorption filter in Example 4 are summarized in Table 3 described below.

[0209] <Example 5>

[0210] As shown in Table 2 described below, in Example 5, a cylindrical adsorption filter was obtained by the same method as in Example 1 except that the powdered activated carbon A was changed to powdered activated carbon E and the blending amount was changed. The results of the physical property measurement and performance evaluation of the adsorption filter in Example 5 are summarized in Table 3 described below.

[0211] <Example 6>

[0212] As shown in Table 2 described below, in Example 6, the same compounding conditions as in Example 1 were used. In Example 6, when molding the adsorption filter, the obtained slurry was sucked at 450 mmHg to 70 mmφ larger than the outer diameter of the mold, and then a rolling process was performed to mold the surface until the outer diameter reached 63 mmφ, and then dried. A cylindrical adsorption filter was obtained in the same manner as in Example 1. The physical property measurement results and performance evaluation results of the adsorption filter in Example 6 are summarized in Table 3 described below.

[0213] <Example 7>

[0214] As shown in Table 2 described below, in Example 7, a cylindrical adsorption filter was obtained by the same method as in Example 1 except that the titanosilicate lead adsorbent was not added. The results of the physical property measurement and performance evaluation of the adsorption filter in Example 7 are summarized in Table 3 described below.

[0215] <Comparative Example 1>

[0216] As shown in Table 2 described below, in Comparative Example 1, a cylindrical adsorption filter was obtained by the same method as in Example 1, except that the powdered activated carbon A was not included and only the powdered activated carbon B was used. The results of the physical property measurement and performance evaluation of the adsorption filter in Comparative Example 1 are summarized in Table 3 described below.

[0217] <Comparative Example 2>

[0218] In the mixing ratio shown in Table 2 described later, powdered activated carbon A, powdered activated carbon B and titanosilicate lead adsorbent were mixed to obtain a total of 1.6 kg of mixed powder. In addition, 0.4 kg of high-density polyethylene powder binder corresponding to the mixing ratio shown in Table 2 described later was added to the mixed powder. Then, the mixed powder was put into a micro-speed mixer (manufactured by Takara Machinery Co., Ltd., "MS-25 type") and stirred for 2 minutes. Next, the obtained mixture was filled into the mold while vibrating the cylindrical stainless steel mold with an inner diameter of 65 mmφ, a core diameter of 30 mmφ, and a height of 90 mm with a lid on one side with a mallet, and the lid was covered on the open side, thereby fixing the contents. The mold filled with the mixture was put into a dryer at 160°C and heated for 120 minutes, and then cooled to below 50°C. Then, the lid was removed and the molded object was pulled out from the mold in a manner that did not damage the molded object. Next, the obtained molded product was cut to produce a dry molded body having an outer diameter of 65 mmφ, an inner diameter of 30 mmφ, and a height of 84 mm. Finally, both ends of the obtained molded body were cut off with a saw to produce an adsorption filter having a height of 64 mm. The results of the physical property measurement and the performance evaluation of the adsorption filter in Comparative Example 2 are summarized in Table 3 described below.

[0219] <Comparative Example 3>

[0220] 100L of tap water and 1.5kg of fibrous activated carbon in dry weight were put into a 100L small-sized beater, followed by a fibrous acrylic binder having a dry weight equivalent to 0.075kg, and the beating was performed. Specifically, the fibrous activated carbon was refined by dispersing and mixing the fibrous activated carbon and the binder, further reducing the gap between the fixed teeth and the rotating teeth of the beater. If the fiber length of the fibrous activated carbon is shortened by the refinement, the filling property is improved when it is molded into a specific shape, and thus the weight per unit volume increases. The weight per unit volume is called the beating density and is used as a measure of the length of the fibrous activated carbon. In order to measure the beating density, the following molded body was produced. Specifically, a 300-mesh metal wire mesh was wound around a central axis with a suction aperture of 3 mmφ and a spacing of 5 mm, and a mold with a central axis diameter of 18 mmφ, an outer diameter of 40 mmφ, and an outer diameter flange spacing of 50 mmH was prepared. The slurry was sucked from the center to produce a cylindrical adsorption filter molded body. The beating density calculated from the size and weight of the dried product of the molded body was 0.183 g / ml. In Comparative Example 3, the slurry with a beating density of 0.183 g / ml was used as the standard slurry.

[0221] In Comparative Example 3, a cylindrical adsorption filter was obtained by the same method as in Example 1 except that a specified amount of powdered activated carbon C was added to the standard slurry in a manner to achieve the mixing ratio shown in Table 2 described later. The physical property measurement results and performance evaluation results of the adsorption filter in Comparative Example 3 are summarized in Table 3 described later.

[0222] <Comparative Example 4>

[0223] In Comparative Example 4, a cylindrical adsorption filter was obtained by the same method as in Comparative Example 2 except that powdered activated carbon D, titanosilicate lead adsorbent, and high-density polyethylene powder binder were used in the mixing ratio shown in Table 2 described below. The physical property measurement results and performance evaluation results of the adsorption filter in Comparative Example 4 are summarized in Table 4 described below.

[0224]

[0225] In the above Table 2, "-" means not contained.

[0226]

[0227]

[0228] in addition, Figure 6 Graphs showing the pore mode diameters and the pore volumes in the regions of the adsorption filters of Examples 1 to 7 and Comparative Examples 1 to 3 measured by a mercury porosimeter are shown in FIG.

[0229] and, Figure 7 The pore volumes (cm2) of the adsorption filters of Examples 1 to 7 and Comparative Examples 1 and 3 with pore diameters of 10 μm or more, measured by mercury porosimetry, are shown in FIG. 3 / cc) and ultrafine particle removal performance (%). In addition, Figure 8 The pore volumes (cm2) of the pores with a diameter of 7 μm or less of Examples 1 to 7 and Comparative Examples 1 and 3 to 4 measured by mercury porosimetry are shown in FIG. 3 As shown in Table 3, the comparative example 2 was stopped midway and is not shown.

[0230] like Figure 7 As shown in Figure 2, the volume of pores with a pore diameter of 10 μm or more is about 0.39 cm 3 / cc or less, it exhibits excellent ultrafine particle removal performance. Figure 8 As shown in the results of this example, the pore volume of the pore with a pore diameter of 7 μm or less is about 0.15 cm 3 / cc or more, it exhibits excellent ultrafine particle removal performance.

[0231] [Investigation]

[0232] As shown in the above Table 3, the adsorption filters of Examples 1 to 7 have excellent ultrafine particle removal performance and maintain good water permeability. In contrast, the adsorption filter of Comparative Example 1 does not meet the qualified standard for ultrafine particle removal performance, and the adsorption filter of Comparative Example 2 does not meet the qualified standard for initial water flow resistance. Comparing Example 1 and Comparative Example 1, although the total pore volume and the pore mode diameter are approximately the same value, the adsorption filter of Comparative Example 1 does not meet both the specified range of pore volume with a pore diameter of 10 μm or more and the specified range of pore volume with a pore diameter of 7 μm or less of the present embodiment. In detail, as Figure 6 As shown, it can be seen that the pore distribution of Comparative Example 1 is more present in the direction of larger pore diameters, specifically, in the range of pore diameters of 10 μm or more, compared with the pore distribution of Example 1. In addition, it can be seen that the pore distribution of Comparative Example 1 is less present in the direction of smaller pore diameters, specifically, in the range of pore diameters of 7 μm or less, compared with the pore distribution of Example 1. Therefore, it can be estimated that there is a difference in the effect of ultrafine particle removal performance. As described above, it can be considered that with respect to the adsorption filters of Examples 1 to 7, the pore volume of the adsorption filters with a pore diameter of 10 μm or more and the pore volume of the pore diameter of 7 μm or less are appropriately controlled.

[0233] This application is based on Japanese patent application No. 2020-167069 filed on October 1, 2020, and the contents are incorporated herein by reference.

[0234] In order to describe the present invention, the present invention is appropriately and fully described above through embodiments and examples with reference to specific examples, but it should be understood that those skilled in the art can easily change and / or improve the embodiments and examples. Therefore, as long as the modified embodiments or improved embodiments implemented by those skilled in the art do not deviate from the protection scope of the claims recorded in the claims, the modified embodiments or improved embodiments can be interpreted as being included in the protection scope of the claims.

[0235] Industrial Applicability

[0236] According to the adsorption filter of the present invention, when used as, for example, a water purification filter or the like, it is possible to exhibit excellent ultrafine particle removal performance while maintaining good water permeability.

Claims

1. An adsorption filter, characterized in that include: A shaped body comprising activated carbon and a binder, wherein The volume-based pore volume of the adsorption filter with a pore diameter of 10 μm or more measured by mercury intrusion porosimetry was 0.10 cm 3 / cc~0.39cm 3 / cc, The volume-based pore volume of the adsorption filter with a pore diameter of 7 μm or less measured by mercury intrusion porosimetry was 0.15 cm 3 / cc or more, and The total pore volume of the adsorption filter measured by mercury intrusion porosimetry was 0.50 cm 3 / cc~0.73cm 3 / cc.

2. The adsorption filter according to claim 1, characterized in that The density of the adsorption filter is 0.59 g / cm 3 the following.

3. The adsorption filter according to claim 1, characterized in that The ratio of the volume-based pore volume of the adsorption filter having a pore diameter of 10 μm or more measured by mercury intrusion porosimetry to the volume-based total pore volume of the adsorption filter measured by mercury intrusion porosimetry is 12% or more.

4. The adsorption filter according to claim 1, characterized in that The ratio of the volume-based pore volume of the adsorption filter having a pore diameter of 7 μm or less measured by mercury intrusion porosimetry to the volume-based total pore volume of the adsorption filter measured by mercury intrusion porosimetry is 22% or more.

5. The adsorption filter according to claim 1, characterized in that The mode diameter of pores measured by mercury intrusion porosimetry was 15 μm or less.

6. The adsorption filter according to claim 1, characterized in that In the carbide obtained by heat-treating the adsorption filter at 900° C. for 20 minutes in an inert gas, the content of particles having a particle size of 10 μm or less is 2% by volume or more.

7. The adsorption filter according to claim 1, characterized in that The saturated adsorption amount of benzene is 18% to 35%, and the saturated adsorption amount of benzene is obtained from the weight increase of the sample when the mass becomes constant while air containing solvent vapor at 1 / 10 of the saturated concentration of the solvent is passed through at 25°C.

8. The adsorption filter according to claim 1, characterized in that In a carbide obtained by heat-treating the adsorption filter at 900° C. for 20 minutes in an inert gas, a 0% particle size in a volume-based cumulative particle size distribution is 7 μm or less.

9. The adsorption filter according to any one of claims 1 to 8, characterized in that The binder includes a fibrous binder.

10. The adsorption filter according to claim 9, characterized in that The fibrous binder includes an acrylic fibrous binder.

11. The adsorption filter according to claim 9, characterized in that The fibrous binder includes a cellulose-based fibrous binder.